2002
DOI: 10.1074/jbc.m111859200
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Selection of RNA Aptamers That Bind to Cell Adhesion Receptors of Trypanosoma cruzi and Inhibit Cell Invasion

Abstract: Trypanosoma cruzi causing Chagas' disease needs to invade host cells to complete its life cycle. Macromolecules on host cell surfaces such as laminin, thrombospondin, heparan sulfate, and fibronectin are believed to be important in mediating parasite-host cell adhesions and in the invasion process of the host cell by the parasite. The SELEX technique (systematic evolution of ligands by exponential enrichment) was used to evolve nuclease-resistant RNA ligands (aptamer ‫؍‬ to fit) that bind with affinities of 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
121
1
7

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(130 citation statements)
references
References 42 publications
1
121
1
7
Order By: Relevance
“…�s interesting examples, members of the Gp85/TS family are developmentally regulated by postranscriptional mechanisms, with Gp82 and Tc85 glycoproteins expressed mainly in the MT and TCT forms, respectively. Gp82 binds to gastric mucin and Tc85 binds to members of the laminin and fibronectin families in the extracellular matrix (ECM); however, other receptors cannot be ruled out as Tc85 molecules have been described as multi-adhesion glycoproteins (Wirth & Kierszenbaum 1984, Ouaissi et al 1984, 1985, Noisin & Villalta 1989, Santana et al 199�, Magdesian et al 2001, Ulrich et al 2002, Nde et al 200�, Yoshida 2008 (Magdesian et al 200�). On the other hand, it has been shown that an inactive form of TS from TCT that binds sialic acid triggers NF-kB activation, the expression of adhesion molecules on endothelial cells and upregulation of parasite entry in a FLY-independent and carbohydrate-dependent way (Dias et al 2008).…”
Section: Signalling Mechanisms and Molecules Involved In T Cruzi Invmentioning
confidence: 99%
“…�s interesting examples, members of the Gp85/TS family are developmentally regulated by postranscriptional mechanisms, with Gp82 and Tc85 glycoproteins expressed mainly in the MT and TCT forms, respectively. Gp82 binds to gastric mucin and Tc85 binds to members of the laminin and fibronectin families in the extracellular matrix (ECM); however, other receptors cannot be ruled out as Tc85 molecules have been described as multi-adhesion glycoproteins (Wirth & Kierszenbaum 1984, Ouaissi et al 1984, 1985, Noisin & Villalta 1989, Santana et al 199�, Magdesian et al 2001, Ulrich et al 2002, Nde et al 200�, Yoshida 2008 (Magdesian et al 200�). On the other hand, it has been shown that an inactive form of TS from TCT that binds sialic acid triggers NF-kB activation, the expression of adhesion molecules on endothelial cells and upregulation of parasite entry in a FLY-independent and carbohydrate-dependent way (Dias et al 2008).…”
Section: Signalling Mechanisms and Molecules Involved In T Cruzi Invmentioning
confidence: 99%
“…A whole series of aptamers that can bind protein targets inside and outside the cell can be found in the literature, which illustrates the potential of DNA or RNA aptamers as therapeutic modalities. Examples include aptamers to HIV related targets (Andreola et al, 2001;de Soultrait et al, 2002;Duzgunes 2001), hepatitis C (Biroccio et al, 2002;Hwang et al, 2000;Vo et al, 2003), Trypanosoma cruzi (Homann and Goringer, 1999;Homann and Goringer, 2001;Ulrich et al, 2002), prion proteins (Sayer et al, 2004;Weiss et al, 1997), thrombin (Bock et al, 1992;Griffin et al, 1993;Holland et al, 2000), anti-angiogenesis vascular endothelial growth factor (Blank et al, 2001;White et al, 2003), prostate specific membrane antigen (Lupold et al, 2002), among many others. Aptamers against the nucleolin are currently in clinical trials for the treatment of cancer with very promising results (www.antisoma.com).…”
Section: Aptamers As Therapeuticsmentioning
confidence: 99%
“…The SELEX technique has been used to isolate high affinity aptamers for a wide range of targets, including small organic molecules (13,14), peptides (15,16), soluble proteins such as growth factors, neuropeptides, (17)(18)(19)(20)(21)(22), cell surface epitopes (23), proteins exposed in their membrane environment (24), red blood cell membranes (25), and whole organisms such as parasites (26,27) and anthrax spores (28). Aptamers with possible future therapeutic importance include aptamers that target pathogens such as the hepatitis C virus (29), the HIV virus (30,31), and African and American trypanosomes (26,27).…”
Section: The Selex Techniquementioning
confidence: 99%
“…Aptamers with possible future therapeutic importance include aptamers that target pathogens such as the hepatitis C virus (29), the HIV virus (30,31), and African and American trypanosomes (26,27). Aptamers have also been shown to effectively block growth factor induced receptor activation.…”
Section: The Selex Techniquementioning
confidence: 99%
See 1 more Smart Citation